Influence of Stochastic Meshing Parameter on Vibration of Shearer Cutting Unit Planetary - Wu Guijun; Zhang Yu; Chen Hongyue; Mao Jun (Jixie chuandong)
In order to research the influence of stochastic meshing parameters on vibration of shearer cutting unit gear transmission system,taking the MG500/1180-WD shearer as the research object,considering about the effects of the factors such as meshing stiffness,meshing damping,combined error and gear backlash,the pure torsion nonlinear dynamics model of gear transmission system for shearer cutting unit is established,takes the meshing stiffness,meshing damping,combined error and gear backlash as the random variable,and also using the variable step size Runge-Kutta methods,the system model is solved,the statistical characteristic for the transient response of the system is obtained through statistic analysis. The research indicates that the mean value and mean-square deviation of the vibration displacement for solar wheel and planet gear increases with the degree of dispersion of the random clearance,meshing error and meshing stiffness,and random clearance has the maximum influence on the vibration displacement of planetary,random meshing stiffness comes second,the least influence is random meshing error. The research results provide the theoretical basis for structural optimization of shearer cutting unit transmission system and improvement of working stability.